2021
DOI: 10.3390/molecules26092662
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Frameworks Based on Rhenium Clusters Using the Synthons Approach

Abstract: The reaction of the K4[{Re6Si8}(OH)a6]·8H2O rhenium cluster salt with pyrazine (Pz) in aqueous solutions of alkaline or alkaline earth salts at 4 °C or at room temperature leads to apical ligand exchange and to the formation of five new compounds: [trans-{Re6Si8}(Pz)a2(OH)a2(H2O)a2] (1), [cis-{Re6Si8}(Pz)a2(OH)a2(H2O)a2] (2), (NO3)[cis-{Re6Si8}(Pz)a2(OH)a(H2O)a3](Pz)·3H2O (3), [Mg(H2O)6]0.5[cis-{Re6Si8}(Pz)a2(OH)a3(H2O)a]·8.5H2O (4), and K[cis-{Re6Si8}(Pz)a2(OH)a3(H2O)a]·8H2O (5). Their crystal structures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Various neutral and anionic ligands have been introduced at the six terminal positions of sulfide-capped octahedral hexanuclear rhenium(III) complexes by thermal substitution reactions of the terminal halides or hydroxides in [Re 6 (μ 3 -S) 8 X 6 ] 4– (X = Cl, Br, I, OH) in solution or under melt conditions (see refs ( 16 , 35 , 37 , 39 , 44 , 45 , 47 − 49 , 52 − 54 , 56 − 58 , 61 , 63 , 65 − 67 , 70 , 71 , 75 , 76 , 83 − 88 )). To our knowledge, several reports have been published on photosubstitution reactions of octahedral hexanuclear metal complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various neutral and anionic ligands have been introduced at the six terminal positions of sulfide-capped octahedral hexanuclear rhenium(III) complexes by thermal substitution reactions of the terminal halides or hydroxides in [Re 6 (μ 3 -S) 8 X 6 ] 4– (X = Cl, Br, I, OH) in solution or under melt conditions (see refs ( 16 , 35 , 37 , 39 , 44 , 45 , 47 − 49 , 52 − 54 , 56 − 58 , 61 , 63 , 65 − 67 , 70 , 71 , 75 , 76 , 83 − 88 )). To our knowledge, several reports have been published on photosubstitution reactions of octahedral hexanuclear metal complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Various neutral and anionic ligands have been introduced at the six terminal positions of sulfide-capped octahedral hexanuclear rhenium­(III) complexes by thermal substitution reactions of the terminal halides or hydroxides in [Re 6 (μ 3 -S) 8 X 6 ] 4– (X = Cl, Br, I, OH) in solution or under melt conditions (see refs , , , , , , , , , , , , , , , , ). To our knowledge, several reports have been published on photosubstitution reactions of octahedral hexanuclear metal complexes. ,, Gray et al reported that the emission lifetime (τ em ) and quantum yield (Φ em ) of a hexanuclear rhenium complex with terminal iodides or solvent molecules in dichloromethane increase in the presence of an added iodide ion or neat solvent molecules [i.e., dimethyl sulfoxide (DMSO)], suggesting the labile nature of the terminal halides in the excited state. , Zheng et al reported that UV irradiation of [Re 6 (μ 3 -Se) 8 (PEt 3 ) 5 {HNC­(OCH 3 ) (CH 3 )}] 2+ in acetonitrile produces [Re 6 (μ 3 -Se) 8 (CH 3 CN) (PEt 3 ) 5 ] 2+ and that of a dichloromethane solution of [Re 6 (μ 3 -Se) 8 (CO)­(PEt 3 ) 5 ] 2+ affords a 23e complex, [Re 6 (μ 3 -Se) 8 Cl­(PEt 3 ) 5 ] 2+ , in which the coordinating chloride ion originates from dichloromethane. , Szczepura et al reported oxazoline and oxazine ligand removal reactions on [Re 6 (μ 3 -Se 8 ) (PEt 3 ) 5 (L)] 2+ (L = 2-methyloxazoline, 2-phenyloxazoline, and 2-methyloxazine) by UV irradiation .…”
Section: Resultsmentioning
confidence: 99%